2022
DOI: 10.21203/rs.3.rs-1387051/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors for Campylobacteriosis in Australia: Outcomes of a 2018–2019 Case-Control Study

Abstract: Background We aimed to identify risk factors for sporadic campylobacteriosis in Australia, and to compare these for Campylobacter jejuni and Campylobacter coli infections. Methods In a multi-jurisdictional case-control study, we recruited culture-confirmed cases of campylobacteriosis reported to state and territory health departments from February 2018 through October 2019. We recruited controls from notified influenza cases in the previous 12 months that were frequency matched to cases by age group, sex, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…However, as most campylobacteriosis in Australia is believed to be foodborne (Vally et al., 2014 ), we can approximate the risk posed by the consumption of meat from a source with the relative attributable proportion, that is, by dividing the proportion of cases attributed to that source by its domestic consumption. Applying this method, we estimate consuming chicken meat posed a 22–27 times greater risk of campylobacteriosis than consuming meat from pigs and ruminants, in accord with the findings of the case–control study (Cribb et al., 2022 ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, as most campylobacteriosis in Australia is believed to be foodborne (Vally et al., 2014 ), we can approximate the risk posed by the consumption of meat from a source with the relative attributable proportion, that is, by dividing the proportion of cases attributed to that source by its domestic consumption. Applying this method, we estimate consuming chicken meat posed a 22–27 times greater risk of campylobacteriosis than consuming meat from pigs and ruminants, in accord with the findings of the case–control study (Cribb et al., 2022 ).…”
Section: Discussionsupporting
confidence: 82%
“…Study data were collected as part of the broader CampySource project, a collaboration between Australian academic institutions, government agencies, and industries. A detailed description of study methods and data collection can be found elsewhere (Cribb et al., 2022 ; Varrone et al., 2018 ; Walker et al., 2019 ; Wallace et al., 2021 , 2020 ). The sequence readset for each food isolate (Bioproject Accession: PRJNA591966), case isolates sampled as part of the case–control study (Bioproject Accession: PRJNA592186), and the case isolates included in the national snapshot (Bioproject Accession: PRJNA560409) are available through GenBank (Clark et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation